Challenges of drug resistance in the management of pancreatic cancer. Issue 10 (October 2010) - Sheikh, Rizwan; Walsh, Naomi; Clynes, Martin; O'Connor, Robert; McDermott, Ray
The current treatment of choice for metastatic pancreatic cancer involves single-agent gemcitabine or a combination of gemcitabine with capecitabine or erlotinib (a tyrosine kinase inhibitor). Only 25–30% of patients respond to this treatment and patients who do respond initially ultimately exhibit disease progression. Median survival for pancreatic cancer patients has reached a plateau due to inherent and acquired resistance to these agents. Key molecular factors implicated in this resistance include: deficiencies in drug uptake, alteration of drug targets, activation of DNA repair pathways, resistance to apoptosis and the contribution of the tumor microenvironment. Moreover, for newer agents including tyrosine kinase inhibitors, overexpression of signaling proteins, mutations in kinase domains, activation of alternative pathways, mutations of genes downstream of the target and/or amplification of the target represent key challenges for treatment efficacy. Here we will review the contribution of known mechanisms and markers of resistance to key pancreatic cancer drug treatments.